How physicians make sense of their experience of being involved in hospital users' complaints and the associated mediation - Béatrice Schaad; Céline Bourquin; Francesco Panese; Friedrich Stiefel (BMC, 2019)
Abstract Background The growing interest in hospital users' complaints appears to be consistent with recent changes in health care, which considers the patient's voice a valuable information source to improve health care. Based on the assumption that the clinicians' lived experience is an essential element of health care and to neglect it may have serious consequences, this study aimed to explore how physicians experience hospital users' complaints and the associated mediation process. Methods A qualitative analysis of experience narrative interviews. Fourteen physicians concerned by complaints which resulted in a mediation provided a comprehensive narrative of their experience with the complaints center. Data were analyzed with Interpretative Phenomenological Analysis (IPA). Interviews were analyzed inductively and iteratively to explore how physicians make sense of their experience. Results The analysis of the physicians' narratives revealed that being the object of a complaint and to enter a process of mediation is a specific experience of which some physicians benefited and others felt psychologically weakened. The causes of the complaints were at times considered by physicians to be related to medical malpractice, but more often to communicational and relational difficulties, unrealistic expectations of patients, physicians' attitudes, or the lack of a coherent care plan. The analysis of their narratives revealed that physicians showed a need for reconsidering and elaborating on the reason(s) leading to the complaint, and on the expectations patients/relatives may have had towards medicine and health care professionals. This may be interpreted as an attempt to assign their meaning, such meaning having the potential to ease the distress associated with the experience of complaints. Conclusion Most physicians appeared more aware of the communicational and relational aspects of care after experiencing a complaint situation; however, prior to the complaint, physicians seem to have underestimate these issues, and when they acknowledge that the complaint originated in psychological aspects of care, they still consider it not relevant, since not related to clinical decision-making and management. Mediation as providing the opportunity to restore the clinical relationship should be encouraged at an institutional level as well as support of health care professionals by means of individual or group supervision.